Conditions of energy efficient behaviour - a comparative study between Sweden and the UK - Pyrko, J; Darby, S (Springer Netherlands, 2011)
The main aim of this study is to compare how specific conditions in certain countries (in this case, the UK and Sweden) can stimulate or oblige householders to be more energy efficient, or can obstruct this. European goals for energy and emission reductions now constitute the main frame for long-term energy policy changes, but national governments develop and implement policy in contrasting ways and in different contexts. Important aspects are: geographical contex, degree of liberalisation of electricity and gas industry, structure and composition of energy systems, metering and billing infrastructure, and the nature of electrical load problems. The following conditions are described and compared in this paper: (1) regulation to control residential consumption and emissions; (2) energy systems; (3) electricity pricing; (4) the role of utilities and other agents in residential demand reduction; (5) quality of feedback on energy use to the householder; and (6) customer behaviour and perceptions of energy use. The analysis is carried out with a view to ecological, economic and social aspects of energy systems. The comparison shows the significance of factors that are sometimes overlooked when considering the potential for demand reduction and load management, and produces some lessons and questions that are widely applicable.